HR TECHNOLOGIES IN PERSONNEL MANAGEMENT AS A COMPONENT OF THE FINANCIAL AND ECONOMIC SECURITY OF ENTERPRISES IN THE CONDITIONS OF DIGITAL TRANSFORMATION - KRAMARENKO, Iryna; NADTOCHII, Iryna; HRYSHYNA, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Today, for some enterprises of Ukraine, there is a threat to their activities associated with active hostilities on a large territory, as well as constant cyber attacks from the Russian Federation. Also, the main factor in ensuring the company's competitiveness is the digital transformation of business processes, which ensures an increase in productivity and efficiency. The use of digital technologies in business requires more and more protection to minimize future threats from information leakage through cyber-attacks or rogue employees. Increasingly, there are cases where personnel are not responsible for disclosing information that poses a threat to the financial and economic activity of the enterprise. That is why there is a need to improve the use of HP technology in management personnel as a component of the financial and economic security of enterprises in the conditions of digital transformation.The method of writing the article is the study of HP technologies in personnel management as a component of the financial and economic security of enterprises in the conditions of digital transformation.The study of HP technologies in management personnel as a component of the financial and economic security of enterprises in the conditions of digital transformation was carried out. The advantages of HP technologies in management personnel are characterized and the importance of increased protection is emphasized. External and internal threats and risks affecting the financial and economic security of the enterprise are considered. It was determined that external threats have an unregulated nature and systematically affect the company's activities. Internal ones, in their situation, are more regulated and have local influence.It is proposed to develop the mechanism of financial and economic security of the enterprise taking into account the methods and tools of personnel management based on HR technologies. It is emphasized that for modern conditions it is important to pay considerable attention to the formation of the personnel management subsystem on the basis of HR technologies as a component of the financial and economic security of the enterprise, which ensures its strengthening. It was determined to increase the protection of information systems used by management personnel to ensure the reduction of leakage of corporate and personal information, which strengthens the financial and economic security of the enterprise.
Keywords: IT technologies in management personnel; financial and economic security; digital transformation; digital economy; society